Characterizing beach intertidal bar systems using multi‐annual LiDAR data. Issue 8 (13th March 2019) - Miles, Andrew; Ilic, Suzana; Whyatt, Duncan; James, Mike R.
Abstract: Intertidal bars are common in mesotidal/macrotidal low‐to‐moderate energy coastal environments and an understanding of their morphodynamics is important from the perspective of both coastal scientists and managers. However, previous studies have typically been limited by considering bar systems two‐dimensionally, or with very limited alongshore resolution. This article presents the first multi‐annual study of intertidal alongshore bars and troughs in a macrotidal environment using airborne LiDAR (light detection and ranging) data to extract three‐dimensional (3D) bar morphology at high resolution. Bar and trough positions are mapped along a 17.5 km stretch of coastline in the northwest of England on the eastern Irish Sea, using eight complete, and one partial, LiDAR surveys spanning 17 years. Typically, 3–4 bars are present, with significant obliquity identified in their orientation. This orientation mirrors the alignment of waves from the dominant south‐westerly direction of wave approach, undergoing refraction as they approach the shoreline. Bars also become narrower and steeper as they migrate onshore, in a pattern reminiscent of wave shoaling. This suggests that the configuration of the bars is being influenced by overlying wave activity. Net onshore migration is present for the entire coastline, though rates vary alongshore, and periods of offshore migration may occur locally, with greatest variability between northern and southern regions of the coastline. This work highlights the need to consider intertidal bar systems as 3D, particularly on coastlines with complex configurations and bathymetry, as localized studies of bar migration can overlook 3D behaviour. Furthermore, the wider potential of LiDAR data in enabling high‐resolution morphodynamic studies is clear, both within the coastal domain and beyond. © 2019 John Wiley & Sons, Ltd. Abstract : A 17.5 km stretch of coastline exhibiting intertidal bars was investigated using nine airborne LiDAR surveys, allowing bar and trough positions to be extracted at a resolution of 2 m alongshore and across‐shore. Bars were found to be oriented obliquely to the shoreline, with orientation varying about a nodal point in sediment transport. They were also seen to become narrower and steeper as they migrated onshore and it is hypothesized that overlying wave processes are the primary driver behind bar configuration.